Va rog, e urgent!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Anexe:
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
Explicație pas cu pas:
1)a = m(3) +2 = m(3) +3 -1 = m(3) -1, m(3)=multiplu de 3
a = m(4) +3 = m(4) +4 -1 = m(4) -1
a = m(6) +5 = m(6) +6 -1 = m(6) -1
a+1 = m(3) = m(4) = m(6)
a+1 = c.m.m.mc (3; 4; 6) =12
a = 12 -1 = 11
2) similar cu 1)
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Franceza,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă